ARTIFICIAL MATURATION STUDY OF A HUMIC COAL AND A TORBANITE - Han Z.; Yang Q.; Pang Z. (My University, 2001)
Artificial maturation experiments on one humic coal and one torbanite were performed using a closed-system pyrolysis. The samples were heated isothermally for 24 h at temperatures between 200°C and 800°C. Mobile products (gas and extractable bitumen) were quantitatively evaluated, and solid reaction residues were microscopically analyzed. With increasing heating temperature, the sample maturity systematically goes up from high volatile bituminous B coal stage (0.77% Rm vitrinite reflectance) to the late anthracite stage (5.02% Rm) of coalification. The thermal evolution process is divided into two phases of dramatic changes and two phases of relatively slow reaction. The fast reaction phases are characterized by a rapid increase of vitrinite reflectance and peak hydrocarbon generation. The first peak hydrocarbon generation phase begins at about 0.9% vitrinite reflectance. Rapid removal of fragments attached to the aromatic ring units in the humic coal results in simultaneous peak generation of both oil and gas. Rapid breakage of C#C bands in the cross-linked aliphatic network of torbanite (especially Botryococcus alginite) leads to the conversion of the entire maceral to liquid products (oil or extractable bitumen); subsequently, thermal cracking of these liquid products results in generation of secondary gas. Therefore, peak gas generation from the torbanite occurs later relative to peak gas generation from the humic coal. The second peak hydrocarbon generation phase occurs during the late anthracite stage (reflectance higher than 3.7%) and is characterized by rapid gas generation and strong reflectance increase. The observation of the second peak hydrocarbon generation phase suggests an economic importance for over-mature kerogen in deeply buried sediments.
Keywords: ARTIFICIAL MATURATION; CLOSED-SYSTEM PYROLYSIS; HYDROCARBON GENERATION; VITRINITE REFLECTANCE; ALGINITE; TORBANITE; HUMIC COAL